Optimal operation of thermal processing of canned tuna under product variability. (September 2021) - Pitarch, J.L.; Vilas, C.; de Prada, C.; Palacín, C.G.; Alonso, A.A.
Abstract: Thermal processing of canned products is subject to variability among the different items in a batch, which results in differences in terms of food quality and safety. Such variability is mainly caused by heterogeneity in the thermal processing unit as well as differences in the quantity of food, its compaction, and the quantity of packing liquid from item to item. Besides, for a proper design of the process operation strategies, different conflicting objectives, such as maximization of product quality and uniformity or minimization of processing time and energy consumption, must be considered. In this paper, we present a suitable formulation to efficiently address the multi-objective optimization problem of thermal processing of canned food under the presence of product variability. Such variability has been characterized from experimental data provided by an industrial cannery. Our formulation exploits the monotonic and convex behavior of the quality/safety indicators and the product kinetics with respect to the uncertain thermal coefficients, avoiding thus the computationally-expensive stochastic approach via Monte-Carlo simulations. In particular, customizable retort temperature profiles are considered as a beneficial alternative to the standard constant retort temperature practice. Highlights: Optimal strategies for tuna sterilization are analyzed from a holistic point of view. Product variability is explicitly considered to achieve optimal and safe operation. Multi-objective optimization unlocks the trade off on average quality and uniformity. Convexity and monotonic features enable efficient computation of thermal treatments. The come-up slope is a relevant decision variable for multi-objective optimization.